2011
DOI: 10.1038/sc.2010.194
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effect of incremental angles of wheelchair tilt on interface pressure among individuals with spinal cord injury

Abstract: Study design: This study was a repeated measures study. Objectives: The objective was to systematically measure the relative reduction in interface pressure (IP) at the ischial tuberosities (IT) and sacrum through 101 increments of tilt in a manual wheelchair among individuals with motor complete spinal cord injury (SCI). Setting: This study was carried out in Manitoba, Canada. Methods: A total of 18 adults with ASIA A or B level of injury were recruited through an out-patient SCI clinic. Using a standardized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…22 These technologies were also used in determining that 30 degrees of wheelchair tilt is needed to relieve pressure from the ischial and sacral areas. 23 Their use in bed-bound patients has been limited but has great potential for determining pressure points at risk for ulceration and in determining the effect of pressure-relieving positions on established wounds.…”
Section: Preventionmentioning
confidence: 99%
“…22 These technologies were also used in determining that 30 degrees of wheelchair tilt is needed to relieve pressure from the ischial and sacral areas. 23 Their use in bed-bound patients has been limited but has great potential for determining pressure points at risk for ulceration and in determining the effect of pressure-relieving positions on established wounds.…”
Section: Preventionmentioning
confidence: 99%
“…Once positioned in the wheelchair, participants were instructed to sit as still as possible for 6 min to allow for appropriate settling time and to allow for sensor creep [4,29]. Interface pressure data were recorded at 1 Hz for 2 min, yielding a total of approximately 120 samples per participant.…”
Section: Data Collectionmentioning
confidence: 99%
“…For example, expression of the interface pressure via the dispersion index allows for objective measure of the evenness of load distribution and has been used to inform clinical recommendations [3]. Features extracted from pressure maps have been useful in a wide variety of clinical applications relevant to wheelchair use, particularly in pressure ulcer prevention and management [4][5][6]. Indeed, objective measures derived from pressure array data are lately considered sufficiently robust as to be utilized as primary outcome measures in randomized clinical trials [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For users who are not able to independently perform such manoeuvres, wheelchairs with incorporated tilt (inclination of complete seat pan and backrest unit) and recline (additional leaning of only the backrest) functions offer the ability to temporarily redistribute weight and reduce sitting pressure [9]. Several wheelchair studies have reported a decrease in sitting interface pressure [1726] as well as an increase in ischial blood flow [18, 27, 28] when tilted and/or reclined, compared to upright sitting. However, all of these studies were performed in cohorts of spinal cord injured patients with only one exception, where healthy young subjects were analysed [20].…”
Section: Introductionmentioning
confidence: 99%